(untitled) (Damascus University Journal of arts and humanities sciences, 2024)
The current study aims to identify the mechanism of adolescent use of social networkers, and to identify the effects of the use of social networks through the mobile phone on the behavior of adolescents away from the control of parents. In addition to defining a new culture for the use of social networks and benefiting from their advantages in an appropriate scientific manner that keeps the adolescent away from isolation from the surrounding milieu. The study relied on the analytical descriptive approach to describe and analyze the phenomenon with all its characteristics and the social survey method, the sample was chosen intentionally. And the sample included (47) respondents in the talshalhab area, distributed between males and famales from the first secondary grade students. The study tool was the questionnaire. The study reached several results, the most important of which are: -All respondents use social networks through their mobile phones, which makes the use of social networks easier and away from family control> -the number of hours the sample used social networks ranged from 3 to 7 hours per day, depending on the social and psychological conditions of each teenager. -the family has a major role in guiding adolescents to social networks, which is represented by the adolescent resorting to parents for help in the situations they exposed to while using social networks and listening to advice given by parents about the dangers of these networks.